2020
DOI: 10.1002/ece3.6779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hedysarum leguminous plants on soil bacterial communities in the Mu Us Desert, northwest China

Abstract: This study assessed the influence of rhizocompartment types (i.e., root, rhizosphere soil, root‐zone soil, and intershrub bulk soil) on the diversity of soil microbial communities under desert leguminous plant shrubs. Moreover, the influence and variations of soil physicochemical factors in interactions among leguminous plants, soil, and microbes were investigated. Both 16S rRNA high‐throughput genome sequencing and conventional soil physicochemical index determination were used to characterize both the bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…In turn, plant roots directly affect the soil portion of the rhizosphere by releasing exudates such as sugars and organic acids, which are sources of nutrients and vitamins used by various bacteria and stimulate the development of microbial communities ( 55 ). Similarly, soil properties can affect root traits, resulting in variations in bacterial communities associated with the root system ( 56 , 57 ). Thus, we conclude that changes in root traits and soil nutrient accumulation in drought-stressed sugarcane varieties contribute to distinct bacterial community compositions, suggesting that ZZ6 may exhibit greater drought resistance than ZZ1 in response to these changes.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, plant roots directly affect the soil portion of the rhizosphere by releasing exudates such as sugars and organic acids, which are sources of nutrients and vitamins used by various bacteria and stimulate the development of microbial communities ( 55 ). Similarly, soil properties can affect root traits, resulting in variations in bacterial communities associated with the root system ( 56 , 57 ). Thus, we conclude that changes in root traits and soil nutrient accumulation in drought-stressed sugarcane varieties contribute to distinct bacterial community compositions, suggesting that ZZ6 may exhibit greater drought resistance than ZZ1 in response to these changes.…”
Section: Discussionmentioning
confidence: 99%
“…The Bonferroni correction was used for all multiple comparisons. Before statistical analysis, the Kolmogorov–Smirnov test of normality and Levene's test of homogeneity of variance were performed on the data (Yan et al, 2018; Zhou et al, 2020). Through one‐way analysis of variance (ANOVA) and the least significant difference test, the soil properties (SOC, TN, TP, AN, NN, AK, AP, pH, clay, silt, sand, BD, and SWC), the fungal diversity index and the relative abundance of all fungi and functional groups were tested.…”
Section: Methodsmentioning
confidence: 99%
“…To elucidate the co‐occurrence network pattern of fungal communities and assess the structural dissimilarities among fungal communities in each plantation, we performed a Spearman correlation analysis on the species composition of the top 50 most abundant fungal genera. Specifically, we considered data points with a correlation coefficient exceeding 0.7 and a p ‐value <0.05 as significant and employed Gephi software to visualize the resulting network patterns (Zhou et al, 2020). All statistical analyses were performed using SPSS 20.0 (SPSS Inc., Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that soil P availability affects and influences the microbial community in roots and soil (Ren et al, 2021). Some reports have shown that soil AP is significantly relevant to the bacterial community of S. davidii, indicating that AP may be an important factor affecting the diversity and composition of the bacterial community in the rhizosphere (Pande et al, 2017;Zhou et al, 2020). It has been found that soil microorganisms can transform the combined phosphorus in soil into water-soluble phosphorus, thus promoting the absorption of phosphorus by plants (He and Zhu, 1998) and shifting the rhizosphere bacterial microbiome (Lennon and Jones, 2011).…”
Section: Important Abiotic Factors Affecting Microbial Community Stru...mentioning
confidence: 99%